Evaluation of Mental Disorders Using Proton Magnetic Resonance Spectroscopy in Dialysis and Predialysis Patients - Chun-Yun Zhang; Ying Chen; Shan Chen; Xiang-Chuang Kong; Yuan Liu; Chao-Qun You; Cheng Wan; Philip A. Bondzie; Hua Su; Chun Zhang; Fang-Fang He (Karger Publishers, 2017)
Background/Aims: Psychological complications are prevalent in patients with chronic kidney disease (CKD). This study aimed to investigate mental disorders in stage 4-5 CKD patients, to detect metabolite concentrations in the brain by proton magnetic resonance spectroscopy (1H-MRS) and to compare the effects of different dialysis therapies on mental disorders in end-stage renal disease (ESRD). Methods: The sample population was made up of predialysis (13), hemodialysis (HD) (13), and peritoneal dialysis (PD) patients (12). We collected the baseline data of patients' age, sex, hemoglobin (Hb) and parathyroid hormone（PTH） levels. The predialysis patients served as the control group. The psychological status of the three groups was assessed using three psychological scales. 1H-MRS was used to evaluate the relative metabolite concentrations in the bilateral amygdala, hippocampus and unilateral anterior cingulated cortex (ACC). Results: The psychological status was better in HD patients than in predialysis and PD patients. 1H-MRS alterations were predominantly found in the ACC. Choline-containing compounds relative to creatine (Cho/Cr), myo-inositol relative to creatine (MI/Cr) and glutamate and glutamine relative to creatine (Glx/Cr) in the ACC were higher in HD patients. 1H-MRS results were correlated with the baseline data and the scores of psychological scales. Conclusions: CKD patients showed different types of mental disorders as well as metabolite disturbances in the brain. The metabolite concentrations correlated with the psychological status which was better in HD than in predialytic and PD patients.